2020
DOI: 10.1371/journal.pone.0232372
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of ultrafast intracranial vessel imaging with non-Cartesian spiral 3D time-of-flight MR angiography at 1.5T: An intra-individual comparison study

Abstract: ObjectivesNon-Cartesian Spiral readout can be implemented in 3D Time-of-flight (TOF) MR angiography (MRA) with short acquisition times. In this intra-individual comparison study we evaluated the clinical feasibility of Spiral TOF MRA in comparison with compressed sensing accelerated TOF MRA at 1.5T for intracranial vessel imaging as it has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…These traits render spiral sequences more robust in terms of several artifacts [6,7,12,13,16,17]. The advantages of spiral MRI were demonstrated in clinical pilot studies for brain and spine imaging [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits render spiral sequences more robust in terms of several artifacts [6,7,12,13,16,17]. The advantages of spiral MRI were demonstrated in clinical pilot studies for brain and spine imaging [8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Spiral sequences offer high k-space sampling efficiency and central k-space oversampling, thus enabling artifact-robust imaging at even shorter scan times than for conventional T1W sequences [6,7]. Spiral sequences have previously shown promise for anatomic and functional imaging of various regions [6][7][8][9][10][11][12][13][14]. However, to our knowledge, the utility of spiral sequences has not been systematically explored for clinical head and neck MRI.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Although we believe that the neuroradiologist with .10 years of experience was professional in drawing ROIs, $2 readers would be better. Sixth, spiral TOF-MRA, which potentially delivers high-quality intracranial vessel imaging at a short scan time, was not included for comparison in the study 28,29 and will be studied in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Recent hardware and software improvements and developments have made spiral MRI feasible for structural MRI on clinical scanners. Accordingly, select clinical pilot studies have explored and shown the value of spiral MRI for brain imaging 8–15 . As in the case of radial sampling, spiral MRI also relies on a non-Cartesian readout scheme thus representing a further advantageous alternative to conventional Cartesian imaging.…”
mentioning
confidence: 99%